The effect of litter separation on methamphetamine-conditioned place preference in post-partum dams. Issue 6 (September 2017) - Lewis, Candace R.; Baker, Allison N.; Fennig, Paulette; Conrad, Phoebe; Hess, Lyndsay; Bastle, Ryan M.; Olive, M. Foster
Abstract : Methamphetamine (METH) abuse among women has recently increased to levels comparable to those observed in men. Although studies using animal models of addiction have begun to include more female subjects, examination of the effects of drugs of abuse on post-partum females is currently lacking. This is especially important in light of the significant hormonal and neurobiological changes that accompany pregnancy and rearing experiences. Furthermore, stress in a known factor in addiction vulnerability and the post-partum experience in the clinical population can be highly stressful. Here, we utilized the conditioned place preference paradigm to investigate the conditioned rewarding effects of METH either in virgin rats or in dams exposed to brief separation (15 min) or long separation (180 min) from the litter. We found that females in the brief separation group showed significantly greater METH conditioned place preference compared with both the long separation and virgin groups. No differences were found in locomotor activity during the conditioning sessions. These findings suggest that peripartum experience and brief litter separation may enhance the rewarding effects of METH.